A systematic review and meta-analysis of efficacy of vasopressin as a vasoconstrictive and uterotonic drug in laparoscopic myomectomy - Amrita Balachandran; R. K. Mishra; A. Ouma Effie; Akshay Raghunathan; Anoopa Mathew; S. Archana (Journal of Minimal Access Surgery, 2024)
Introduction Laparoscopic myomectomy is a commonly performed operation with fast recovery and excellent results. However, haemorrhagic nature of the operation mandates us to use variety of vasoconstrictive and uterotonic agents. Amongst which, one of them is vasopressin. It is a synthetic antidiuretic hormone analogue which has been in common use as a vasoconstrictive agent in various surgical procedures including laparoscopic myomectomy. Methods A meta-analysis of randomised controlled trials published from 2013 to 2023 (10 years) comparing the use of vasopressin against other drug or placebo or different doses of vasopressin was performed. The outcome measures were intraoperative blood loss, need for blood transfusion, difference in the haemoglobin (Hb) and haematocrit (Hct). Results We identified 176 articles through the study search, amongst which 12 articles were included for the meta-analysis. There was a significant heterogeneity in the studies with moderate risk of bias in eight studies and low risk of bias in four studies. Compared to placebo, vasopressin showed significantly lower odds need of blood transfusion (odds ratio [OR] 0.28, 95% confidence interval [CI]: 0.13–0.61, P = 0.002) and significantly lower pre–post fall in Hb (OR −3.12, 95% CI: −4.63–−1.60, P < 0.0001). However, there was no statistically significant difference in intraoperative blood loss (OR −0.56 (95% CI: −2.04–0.92, P = 0.46) and pre–post fall in Hct (OR −0.94, 95% CI: −1.96–0.07, P > 0.05). Compared to other drug (epinephrine, misoprostol and octreotide acetate), vasopressin showed no significant superiority in controlling blood loss (P > 0.05). Even the two doses of vasopressin (dilute vs. concentrated) showed no statistically significant difference between surgical blood loss and need for blood transfusion (P > 0.05). Conclusion Vasopressin is an efficacious drug to be used for controlling blood loss, decreasing blood transfusion requirement and maintaining Hb and Hct during laparoscopic myomectomy.